Relationship between eating habits, physical activity and obesity in children from Majadas de Tiétar (Spain). - Sergio Toro Martín; Alvaro Toro Martín (Archives of Nursing Research, 2022)
Objective: To know the existing relationship of eating habits and physical exercise with obesity. Methodology: The population is of 52 children between 6 and 15 years of age resident in Majadas de Tiétar (Extremadura, Spain). The weight and height of each participant was determined and the body mass index (BMI) was calculated, and compared with the percentile tables of the Orbegozo Foundation to obtain the individual percentile. The KidMed test was used to determine the degree of adhesion to the Mediterranean diet (MD), while the PAQ-A questionnaire for was used for the adolescents and the PAQ-C questionnaire for the younger children to find out the degree of physical activity. Principal results: The prevalence of obesity was 5.77%. The mean score of the KidMed was 4.92 for boys and 3.21 for girls. In the questionnaires on physical activity (PAQ-A & PAQ-C), the mean score was 3.13 for boys and 2.31 for girls. Only 9.6% of the participants showed a high adherence to the Mediterranean diet, while 44.2% had a very low quality diet and 46.2% had a diet that needed improving. Conclusion: There was evidence of the need to make the habits of this population healthier.